2018
DOI: 10.1097/cji.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Hemofiltration Successfully Eliminates Severe Cytokine Release Syndrome Following CD19 CAR-T-Cell Therapy

Abstract: Cytokine release syndrome (CRS) remains to be a major adverse effect of chimeric antigen receptor T (CAR-T) cell therapy in B-cell acute lymphoblastic leukemia (B-ALL) and lymphoma. It was urgent to explore novel strategy for managing severe CRS. We conducted a clinical trial to assess the safety and efficacy of CD19-targeting CAR-T-cells in the treatment of relapsed and chemotherapy-refractory B-ALL and lymphoma. A 10-year-old boy with B-ALL who never achieved minimal residual disease (MRD) negative status af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…We mainly use anti-IL-6 monoclonal antibodies to treat CRS, such as tocilizumab and siltuximab. Some studies have shown that therapeutic plasma exchange (TPE) may be the other option [ 13 ]. The use of glucocorticoids is also one of the main therapeutic methods, which are generally used to supplement anti-IL-6 therapy [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We mainly use anti-IL-6 monoclonal antibodies to treat CRS, such as tocilizumab and siltuximab. Some studies have shown that therapeutic plasma exchange (TPE) may be the other option [ 13 ]. The use of glucocorticoids is also one of the main therapeutic methods, which are generally used to supplement anti-IL-6 therapy [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…gov number, NCT03156101). 13 End points for this study included safety, overall survival, duration of response, and CD19 CAR-T cellular kinetics. These patients were subjected to lymphodepleting chemotherapy with fludarabine (25 mg/m 2 body surface area per day) for 3 days, and cyclophosphamide (500 mg/m 2 body surface area per day) for 2 days, followed by infusion of CD19 CAR-T cells after 3-5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Production of CAR-expressing T cells were produced for the experiments as previously described. 13 Patients and healthy donors provided written informed consents according to the Declaration of Helsinki presented at the International Conference on Harmonization Guidelines for Good Clinical Practice. All relevant ethical regulations were followed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Solely one case report described a similar clinical aggravation of coagulopathy in a patient receiving TCZ after developing CRS secondary to CAR-T cell therapy and bacterial superinfection was suspected to be responsible. [19] In our patient PCT levels were normal before both administrations and broad spectrum antibiotic was applied prophylactically. Nevertheless, septic shock due to fungal pneumonia cannot be ruled out.…”
Section: Discussionmentioning
confidence: 46%